The antiulcer effect of Cibotium barometz leaves in rats with experimentally induced acute gastric ulcer - Al-Wajeeh, N.S.; Hajrezaei, M.; Al-Henhena, N.; Kamran, S.; Bagheri, E.; Zahedifard, M.; Saremi, K.; Noor, S.M.; Ali, Hapipah Mohd; Abdulla, Mahmood Ameen (Dove Medical Press, 2017)
Cibotium barometz is a pharmaceutical plant customarily used in traditional medicine in Malaysia for the treatment of different diseases, such as gastric ulcer. The gastroprotective effect of C. barometz leaves against ethanol-induced gastric hemorrhagic abrasions in Sprague Dawley rats has been evaluated in terms of medicinal properties. Seven groups of rats (normal control and ulcerated control groups, omeprazole 20 mg/kg, 62.5, 125, 250, and 500 mg/kg of C. barometz correspondingly) were used in antiulcer experiment and pretreated with 10% Tween 20. After 1 hour, the normal group was orally administered 10% Tween 20, whereas absolute alcohol was fed orally to ulcerated control, omeprazole, and experimental groups. Gastric’s homogenate were assessed for endogenous enzymes activities. Stomachs were examined macroscopically and histologically. Grossly, the data demonstrated a significant decrease in the ulcer area of rats pretreated with plant extract in a dose-dependent manner with respect to the ulcerated group. Homogenates of the gastric tissue exhibited significantly increased endogenous enzymes activities in rats pretreated with C. barometz extract associated with the ulcerated control group. Histology of rats pretreated with C. barometz extract group using hematoxylin and eosin staining exhibited a moderate-to-mild disruption of the surface epithelium with reduction in submucosal edema and leucocyte infiltration in a dose-dependent manner. In addition, it showed heat shock protein70 protein up-expression and BCL2-associated X protein downexpression. These outcomes might be attributed to the gastroprotective and antioxidative effects of the plant.